1983
DOI: 10.1111/j.1600-0897.1983.tb00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Rat Male Accessory Glands Autoantigens by Affinity Chromatography*

Abstract: The autoantigens of rat male accessory glands were isolated by a short procedure which involved 1) immunization of rats with chemically modified rat male accessory glands' saline extract; 2) purification of immunoglobulin G (IgG) from the autoantisera by chromatography on DEAE-Sephadex A-50;3) coupling of rat IgG anti-rat male accessory glands with 4-B activated Sepharose; 4) addition of rat male accessory glands' saline extract and removal of autoantigens by glycine-HCl, pH 2.9. The purity of the eluted autoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
1988
1988

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…It should be noted, however, that the antisera used in most studies have been generated in a foreign species and that the components identified may not be antigens in terms of the host. Nevertheless, some putative autoantigens have been identified that are produced by the epididymis (Vernon et al, 1982) and the male accessory sex glands (Pesoa et al, 1983). Also, most studies have not ruled out the possibility of contributions by sperm to male excurrent duct fluids used for immunization or assays, but one study has demonstrated that epididymal fluid from immature rats and from seminal vesicles, which have not been in contact with sperm, contains components also detected on ejaculated sperm from mature rats (Dravland and Joshi, 1981).…”
Section: Antisera Have Been Used To Study the Role Of Epididymal Secrmentioning
confidence: 97%
“…It should be noted, however, that the antisera used in most studies have been generated in a foreign species and that the components identified may not be antigens in terms of the host. Nevertheless, some putative autoantigens have been identified that are produced by the epididymis (Vernon et al, 1982) and the male accessory sex glands (Pesoa et al, 1983). Also, most studies have not ruled out the possibility of contributions by sperm to male excurrent duct fluids used for immunization or assays, but one study has demonstrated that epididymal fluid from immature rats and from seminal vesicles, which have not been in contact with sperm, contains components also detected on ejaculated sperm from mature rats (Dravland and Joshi, 1981).…”
Section: Antisera Have Been Used To Study the Role Of Epididymal Secrmentioning
confidence: 97%
“…The present investi gations were initiated preparing from RAG a homo geneous preparation of the antigen under study [7] for both chemical and immunological research.…”
Section: Discussionmentioning
confidence: 99%
“…The purified antigen was obtained as described previously by immunoaffinity chromatography, using the autologous anti-RAG serum as ligand [7]. This material was chemically modified as de scribed for MRAG.…”
Section: Antigensmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical modification does not change the specificity but plays an adjuvant role (10). The autologous antigen involved in that response, as purified by affinity chromatography, appears late in the ontogeny and is not present in females (12). Further reports appeared describing the involvement of the immunoregulatory mechanisms in this phenomenon (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%